The ecology of elephant dung associated dung beetles in Peninsular Malaysia / Thary Gazi - Thary , Gazi (2021)
The loss of large mammals such as Asian Elephants (Elephas maximus) can potentially disrupt the trophic structure for ecosystems that depend on the dung produced by these animals. This can cause a restructuring of the dung beetle community as it may result in less resources for food and breeding and higher intra- and interspecific competition. Dung beetles utilise dung in different manners, and this leads them to be categorised as dwellers, tunnelers or rollers. These categories of beetle likely have different reactions to changes in resource availability. For this study I 1) Designed a method to collect large numbers of dwelling and tunnelling dung beetles, 2) examined the effects of habitat type on the diversity and abundance of elephant dung visiting dung beetles, 3) determined the effects of elephant removal on the community structure of dwelling and tunneling dung beetles and 4) quantified if changes in resource availability affects the phenotype of six common dung beetle species. A novel dung beetle trap, the burrowing interception trap, was designed and the dung beetle collecting performance was compared with conventional pitfall traps. For objectives (2) and (3), dung beetles were sampled from six localities in Peninsular Malaysia, half of which had elephants absent because of human elephant conflict relocations. Both forest edges and forests were sampled to take into account the effects of habitat. Dung beetles were categorised as forest edge or forest species based on their distribution amongst the two habitat types. Between two localities with similar forest structure and elevation but different presence/absence of elephants, I compared intraspecific pronotum sizes of six species of dung beetles. Burrowing interception traps could collect higher abundance, species richness and Shannon diversity but were not effective in collecting roller dung beetles compared to pitfall traps. A total 5413 individuals from 50 tunnelling and dwelling dung beetle species were collected in all localities. Habitat selection of dung beetles played an important role in community assembly, with 10 species categorised as preferring forest edge environments to forests. Forests also had higher abundance and species richness compared to forest edges. Generalised linear models indicated a a positive relationship between the abundance of dwellers and the presence of elephants. At least two species, Megatelus brahminus and Copris numa, were found to be absent when elephants were removed, both were forest edge species. When the intraspecific pronotum widths were examined, two dweller species, Liatongus femoratus and Oniticellus tessellatus, had significant differences in pronotum size, while four tunneler species did not. The loss of elephant dung likely causes a shift from dweller dominated to tunneler dominated communities as an environment with excess resources changes to one of limited and rapidly depleted resources. Aside from extinction, it is possible that some species undergo phenotypic change in order to survive the change in resource availability. This study indicates that the relationship between elephants and dung beetles is a complex interaction that depends on behavioural adaptations of all species and environmental factors.